The Remarkable 2018 "Velvet Revolution": Armenia's Experiment Against Government Corruption. (4th July 2019) - Feldman, Daniel L.; Alibašić, Haris
Abstract : In 2018, massive street protests against its corruption forced the long-dominant political party in Armenia to relinquish power to its nemesis, who himself had been imprisoned for leading protests ten years earlier. The peaceful transition earned the name the "Velvet Revolution." The new Armenian government hosted the principal author of this essay at a week-long conference on anticorruption policy in Yerevan, its capital, with judges, prosecutors, and investigators selected for their integrity and competence. Based on the attitudes and concerns they expressed, publicly available documents reflecting years of research on the Armenian government and corruption and the circumstances of the Velvet Revolution, the authors sought to determine whether particular background conditions and/or characteristics of the peaceful rebellion were especially conducive to the successful implementation of a more fully democratic leadership, opposed to corruption and committed to the rule of law. In the literature addressing such questions in other national contexts, the authors found a similar pattern of background conditions and characteristics, leading to their conclusion that such elements can indeed foster successful transitions. Further research should assess future developments in Armenia, and determine how widely the lessons of its experience can be applied.